RANCANG BANGUN SISTEM INFORMASI INVENTARIS KOLEKSI PADA MUSEUM TEKSTIL JAKARTA - Gandama Fajar Harapan; Agus Wismo Widodo (Fakultas Teknik Universitas Persada Indonesia YAI, 2021)
The development of information technology is currently very rapid, where computers play an important role invarious fields, one of which is processing inventory data. Inventory is an activity or action to carry out physicalcollection of existing assets (collection inventory) in an integrated manner in the management of propertyownership data. The Jakarta Textile Museum is a cultural heritage that houses various collections of Indonesianfabrics and batik tools, which act as an Indonesian textile sanctuary institution and a documentation and research center for traditional Indonesian textiles. Inventory data processing to create a collection of labels to be exhibited at the Jakarta Textile Museum is still done manually, where the technical and administrative data obtained are entered into Microsoft Excel. In the manual processing of inventory data, problems were found such as insufficient or incomplete data. Based on this explanation, the author makes a Final Project report with the title